Integration of Simulation Based Education in Nursing and Midwifery Education - Pandey Bista, Archana (Journal of Nursing Education of Nepal, 2022)
Simulation-Based Education (SBE) has been more prioritized among universities in their specialized health courses like as medicine, nursing and midwifery at different level. Evidences have proved that SBE helps students to acquire knowledge, attitude and skills into structured non-threatening environment which equipped them for clinical practice with more confident, less clinical errors resulting into better health outcome of their patient and client. Integration of structure curriculum is essential for implementing SBE where educators can facilitate their students for quality education which can transfer into quality practice during preservice courses.